Effects of anticoagulation on markers of activation of clotting following major orthopedic surgery. (15th May 2015) - Bern, M. M.; Hazel, D.; Reilly, D. T.; Adcock, D. M.; Hou, L.
Summary: Introduction: This study examines makers of activation of clotting following three chemoprophylactic regimens used for prevention of postoperative venous thromboembolic disease (TED) following high‐risk surgery for TED. Methods: Patients having elective primary knee or hip replacement surgery received variable dose warfarin (target international normalized ratios 2.0–2.5), 1 mg warfarin daily starting 7 days preoperatively or aspirin 325 mg daily starting on the day of surgery. Twelve patients in each group were treated for 28 ± 2 days. Thrombin–antithrombin (T‐AT) and prothrombin fragment F1 + 2 were measured at baseline and postoperative days 3 and 28 ± 2. Results: Thrombin–antithrombin and F1 + 2 on postoperative day 3 were equal for the study groups. By days 28 ± 2, variable dose warfarin therapy group suppressed production of F1 + 2 ( P  = 0.002) with no difference in the T‐AT accumulation. F1 + 2 for other patients overlapped the normal range. Conclusion: The signals of activated clotting following surgery did not differentiate the three regimens on postoperative day 3. Variable dose warfarin was associated with suppression of F1 + 2 after 1 month of therapy, with no effect on accumulation of T‐AT. Fixed low‐dose warfarin started 7 days prior to surgery and aspirin are not inferior on postoperative day 3, but appear to be inferior over a longer treatment.